Nutrient Uptake and Quality of Sweet Corn as Influenced by Drip Lateral Spacing and Fertigation Levels - NAIK, V R; PATEL, J M; NAIK, J R; PATIL, R G (Journal of the Indian Society of Coastal Agricultural Research, 2017)
A field experiment was conducted consecutively for two years (2007-08 and 2008-09) during rabi seasons at Soil and Water Management Research Farm, Navsari Agricultural University, Navsari (Gujarat). In all 10 treatments, comprising nine combinations arising out of three levels each of lateral spacing (L1: 1.2 m, L2: 1.8 m and L3: 2.4 m) and fertigation (F1: 60%, F2: 80% and F3: 100% RDF i.e.120:60:60 kg NPK ha and one surface control (1.00 IW/CPE ratio + 100% RDF) were tested in factorial RBD with four replications. The L1 among lateral spacing and F3 among fertigation rates recorded significantly higher values of total uptake of N, P and K by sweet corn. The combination L1F3 registered significantly higher values of N, P and K uptake by sweet corn as compared to rest of the combinations. The surface control recorded higher uptake of N, P and K in comparison to drip mean. However, it was significantly less than the best drip treatment (L1F3). Further, there was no effect of treatments on distribution of N, P and K in different components of sweet corn. However, proportion of N and P removal through grain was more than stover and husk and that of K was more by stover. Protein content in sweet corn grain was not affected significantly due to main effect of lateral spacing and fertigation as well as their interactive effect. But, total sugar, reducing sugar and non-reducing sugar content in sweet corn grain were conspicuously affected only due to main effect of fertigation. In all the cases, viz., total sugar (28.76%), reducing sugar (3.80%) and non-reducing sugar (23.71%), F3 recorded significantly higher values in comparison to F1 and F2.